ANALISIS PENURUNAN LAPISAN TANAH DASAR (SUBGRADE) JALAN SEMARANG – DEMAK ( STA 0 + 300 s/d 2 + 000) - Annas Firman (LPPM Universitas Pekalongan, 2022)
Roadway planning and construction has undergone a revolution or change in recent years. Many of the more accessible areas, mainly plantation and industrial areas, are located in lowlands where soft soil is found. The Semarang - Demak road section is passed by heavy vehicles, so that it can result in road subsidence. he purpose of this study was to determine the total subgrade subgrade on the Semarang - Demak road section based on PLAXIS calculations with manual calculations. This research was conducted on the Semarang – Demak highway STA 0 + 300. Based on the research conducted, there are differences between manual calculations and calculations using the Plaxis program, the difference can be caused by several factors. In manual calculations caused by the number of calculations so that there are calculations that are less valid and can affect the calculation results. While the plaxis calculation is caused by the amount of data that needs to be entered into the plaxis calculation so that it affects the calculation results.